Limestone Industry on PM2.5 Air Quality in Padalarang and Surrounding Areas - Yuningsih, Nani; Simbolon, Luga Martin; Hidayat, Syarif; TRITJAHJONO, Rachmad Imbang; Sumeru, Husain Akbar; Raji, Lukman (Bandung State Polytechnic (Politeknik Negeri Bandung), 2024)
The processing of limestone through the combustion process will cause air pollution at the combustion site and its surroundings. At the limestone processing site, Padalarang experiences relatively high air pollution. PM2.5 is one of the main pollutants produced by limestone burning, so it is very necessary to study the concentration of PM2.5 in the air in Padalarang and its surroundings. This study was conducted in Padalarang and its surroundings, where data collection was carried out in five locations, namely at the center of limestone burner, 1 km, 2 km, 3 km, and 4 km to the east of the burning center. Data collection was carried out for ten days, where each data collection was carried out for 12 hours, from 07.00 to 19.00. Based on the national standard of PPRI No. 22 of 2021, which is 55 µg/m3, the concentration in the limestone burning center and 1 km from burning center have exceeded the standard, which is 82.5 and 69.3 µg/m3. While PM2.5 concentrations at distances of 2 km, 3 km, and 4 km are below the national standard, namely 52.0, 51.6 and 50.2 µg/m3, respectively. Based on the Air Quality Index (AQI), the AQI at the burning center, distance of 1 km, 2 km, 3 km, and 4 km are Unhealthy, Unhealthy, Moderate, Moderate and Moderate, respectively. This means that areas less than 1 km away are not healthy places to live. The poor air quality in Padalarang is reflected in the much higher number of ARI cases compared to the surrounding sub-districts that do not have a limestone industry.